PENERAPAN KURIKULUM TINGKAT SATUAN PENIDDIKAN (KTSP) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH - Mubarak, Ahmad Zaki (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
Teachcrs are the key people for the success of KTSP curriculum implementation. This isbeiause teachers are the implanters of the curriculum" Even the best curriculum and the best educational system vzill not work unless withthesupportofgoodqualiryteaclrers.lnshort,increasingthequalityof e<lucation in Indonesia strouto ue uottr involving curriculum improvement arrd teachers, quality improvement. so, professional teachers is a must. According to the Act no. 14 year 2005 about teachers and lecturers chapter ll0;.2, a professional teacher should have four competencies; pedagogic, personality, social, and professional. A professional teacher reflects a figure ofteacher who has a broadiorizon about education both macro and micro